INCREASE OF EFFICIENCY OF SHELL-AND-TUBE HEAT EXCHANGERS BY IMPROVEMENT OF STRUCTURAL DESIGN OF INTERTUBE SPACE - A.A. Davronbekov (Journals Park Publishing, 2023)
This article investigates the intricacies of shell and tube heat exchangers (CTA) commonly used in the chemical and oil and gas industries. It delves into the complexities arising from the implementation of flat transverse baffles within these heat exchangers, impacting coolant flow and heat transfer efficiency. The study aims to evaluate the influence of radial clearances between these baffles and the casing on thermal and hydraulic characteristics. Additionally, it addresses the formation of stagnant zones due to flow direction changes, which can lead to overheating and surface deposits, subsequently affecting heat transfer efficiency. By focusing on these factors, the research aims to enhance the understanding of design complexities and challenges to optimize the efficiency of heat exchange processes in shell and tube heat exchangers. This article encapsulates the focus and objectives of the research, emphasizing the investigation into the impact of baffles, radial clearances, and flow dynamics on heat transfer efficiency in shell and tube heat exchangers. Adjustments can be made to include specific methodologies or additional focal points of the study if needed.
Keywords: Shell and Tube Heat Exchangers (CTA), Transverse Baffles, Thermal Efficiency, Hydraulic Characteristics, Radial Clearances, Coolant Flow Dynamics, Stagnant Zones, Heat Transfer Efficiency, Overheating, Surface Deposits, Flow Direction Changes, Oil and Gas Industry, Chemical Industry, Rheological Properties.